Improving the Ability to Read the Qur'an For Elementary School Age Children Using Iqra' Method with Letters Card Media - Usiono, Usiono; Irfan, Muhammad; Zahara, Aida; Winarti, Wiwik; Arafah, Siti; Nuhara, Wenti (Jurnal Basicedu, 2021)
The problem discussed in this study is how to improve the ability to read the Qur'an in elementary school age children through the application of the iqro' method with letter cards. The purpose of this study was to determine the ability to read the Qur'an of elementary school age children through the application of the iqro' method. Problems encountered in grade 1 SD IT Ali Mahfudz. Titi Harapan is that children do not know the hijaiyah letters, distinguish the hijaiyah letters and pronounce the hijaiyah letters correctly. Therefore, the researcher aims to describe the iqro method with letter cards that can attract children's interest. Thus, researchers hope that children will increase their understanding in the field of reading the Koran. The results of this study concluded that the implementation of learning with the iqro' method can improve the ability to read the Qur'an. It can be seen that children are more enthusiastic and cheerful when doing Iqra 'activities with letter card media. Children are more enthusiastic about using the Iqra' method with letter card media with more attractive color modifications